2017
DOI: 10.5688/ajpe6005
|View full text |Cite
|
Sign up to set email alerts
|

Nordic Pharmacy Schools’ Experience in Communication Skills Training

Abstract: Objective. To assess communication skills training at Nordic pharmacy schools and explore ways for improvement.Methods. E-mail questionnaires were developed and distributed with the aim to explore current practice and course leaders' opinions regarding teaching of patient communication skills at all the 11 master level Nordic (Denmark, Finland, Iceland, Norway and Sweden) pharmacy schools. The questionnaires contained both closed-and open-ended questions.Results. There was a variation of patient communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…All schools reported providing training in the teacher survey by Svensberg and colleagues, whereas many students from this study were frustrated at not having received any training at all, or only in the PPE. 21 This indicates that students and teachers conceptualize PCST differently. Similarly, 21 Further, this study showed that few students thought they had received enough and appropriate feedback.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All schools reported providing training in the teacher survey by Svensberg and colleagues, whereas many students from this study were frustrated at not having received any training at all, or only in the PPE. 21 This indicates that students and teachers conceptualize PCST differently. Similarly, 21 Further, this study showed that few students thought they had received enough and appropriate feedback.…”
Section: Discussionmentioning
confidence: 99%
“…21 This indicates that students and teachers conceptualize PCST differently. Similarly, 21 Further, this study showed that few students thought they had received enough and appropriate feedback. Feedback was mentioned in several of the open-ended questions as highly valuable and students asked for more individual feedback, both at their pharmacy school and during the PPE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations